The Mosaics of Via Olmetto, Milan (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2016)
A project of valorisation of the Roman mosaics discovered in the 1970s in Vicolo S.Fermo – Via Olmetto, and now stored in an underground compartment in Via Amedei 4, has arisen the need for a detailed archive research, in order to get all the available information on the recovery places and conditions of each mosaic. The analysis of the documents stored has allowed us to “retrace” the sequence of the different excavation operations. It has also made possible to know the methods chosen to store the mosaics, allowing a better reading and comprehension of the remains. Through the comparison with the data coming from a recent excavation in Via Amedei 2, we can suppose the existence, from IV-V cen. AD, of a great domus, whish resulted from the expansion of a previous building dating back to the imperial age.
Keywords: Milan; via Olmetto; mosaics; domus; archive